Meningkatkan Kualitas Pendidikan Melalui Supervisi Pendidikan yang Efektif - Ulum, Fachrurizal Bachrul; Ni’am , Syukron; Nurhuda, Abid; Huda, Ali Anhar Syi'bul (CV. Lentera Literasi Indonesia, 2025)
Efforts to continuously improve the quality of education and its professionalism continue. One of them is the existence of a managerial model style from the principal and supervisor in the form of supervision. This can be an indicator of the effectiveness of the implementation of education and its performance. And the purpose of this study is to describe related to Improving the Quality of Education Through Effective Educational Supervision. The method used is qualitative with a literature study approach and analyzed descriptively. The results showed that educational supervision is a process of guidance from the principal or supervisor to teachers and school personnel to improve learning situations effectively with the aim that teachers become more professional in carrying out their duties to serve their students. In addition, it plays a role in professional development, motivation, and monitoring the quality of education. And must adhere to scientific principles, democratic principles, principles of cooperation, and constructive and creative principles. There are several steps that must be taken, including choosing a supervision model, whether conventional or traditional, clinical model, scientific model, or artistic model, then carrying out the stages of supervision consisting of: planning, implementation, evaluation, and follow-up.